Smooth Muscle Strips for Intestinal Tissue Engineering - Walthers, Christopher M. (PLoS One, 2014)
Functionally contracting smooth muscle is an essential part of the engineered intestine that has not been replicated in vitro. The purpose of this study is to produce contracting smooth muscle in culture by maintaining the native smooth muscle organization. We employed intact smooth muscle strips and compared them to dissociated smooth muscle cells in culture for 14 days. Cells isolated by enzymatic digestion quickly lost maturity markers for smooth muscle cells and contained few enteric neural and glial cells. Cultured smooth muscle strips exhibited periodic contraction and maintained neural and glial markers. Smooth muscle strips cultured for 14 days also exhibited regular fluctuation of intracellular calcium, whereas cultured smooth muscle cells did not. After implantation in omentum for 14 days on polycaprolactone scaffolds, smooth muscle strip constructs expressed high levels of smooth muscle maturity markers as well as enteric neural and glial cells. Intact smooth muscle strips may be a useful component for engineered intestinal smooth muscle.